Atmospheric Pressure Plasma Grafting of a Vinyl-Quaternary Compound to Nonwoven Polypropylene and Cotton. Issue 3 (September 2018) - Cornelius, Carrie; McCord, Marian; Bourham, Mohamed; Hauser, Peter
Nonwoven polypropylene and cotton fabrics are grafted to a vinyl quaternary compound using atmospheric-pressure plasma. Two different atmospheric plasma devices are used -the NCAPS (North Carolina Atmospheric Plasma System), a dielectric barrier discharge device created by North Carolina State University, and a plasma device from APJeT ® Inc. The addition of additives such as Mohr's salt, potassium persulfate, and diacrylates are assessed to see if graft yield can be increased. Acid dye tests, SEM, and XPS reveal successful grafting of the vinyl quaternary compound. A combination of all four additives is found to yield the highest graft yields and greatest uniformity.